Pengaruh Limbah Kangkung dan Ampas Tahu Terfermentasi dalam Ransum terhadap Konsumsi dan Kecernaan Kalsium serta Fosfor pada Babi Peranakan Landrace Fase Grower-Finisher - Fone, Faustina; Dodu, Tagu; Maranatha, Grace (Animal Agricultura, 2025)
This study aimed to evaluate the effect of including fermented water spinach and tofu waste in diets on the intake and digestibility of calcium (Ca) and phosphorus (P) in Landrace crossbred pigs at the grower–finisher phase. Twelve pigs aged 3–4 months with initial body weights of 30.00–49.00 kg were assigned to a randomized block design with four treatments (R0: control; R1: 10% inclusion; R2: 15% inclusion; R3: 20% inclusion) and three replications. Data were analyzed using ANOVA. The results showed that up to 20% inclusion of fermented water spinach and tofu waste had no significant effect (P>0.05) on calcium intake, calcium digestibility, or phosphorus intake, but significantly decreased (P<0.05) phosphorus digestibility. It can be concluded that the addition of up to 20% of these ingredients is safe for use in pig diets without reducing mineral intake, although attention should be paid to phosphorus digestibility.